Migration processes in Kazakhstan: Trends, specifics, factors - Mussina, S.T.; Khusainova, Zh.S.; Vechkinzova, Y.A. (BUKETOV BUSINESS REVIEW, 2020)
Object: to identify the main trends in external and internal migration in Kazakhstan, to study the characteristics of its different flows, and to describe the economic and demographic factors affecting migration processes. Migration processes in the Republic of Kazakhstan Methods: methods of system, dynamic and structural analysis, and methods of studying cause-andeffect relationships. Results: We have identified trends in external and internal migration in Kazakhstan in the last decade; we have studied the characteristic features of migration flows in Kazakhstan and the factors affecting the migration activity of the population; we have addressed the issue of unregulated migration in Kazakhstan and described the risks associated with it, as well as the possibility of migration policies in addressing this issue. Conclusions: In recent years, the negative balance of external migration has been growing; there is a net outflow from Kazakhstan. The intensity of ethnic repatriation of Kazakhs, which previously would block the flow of emigration, is now decreasing. Measures are needed to halt the outflow of migrants from Kazakhstan and to encourage immigration into Kazakhstan. In recent years, the state has been actively pursuing an internal migration policy: mechanism for registering migrants within the country has been strengthened, and a quota has been established for resettlement to the northern and north-eastern regions of Kazakhstan.